2020
DOI: 10.1016/j.nanoen.2020.104944
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh piezoelectricity in lead-free piezoceramics by synergistic design

Abstract: Following increased environmental concerns on the toxicity of lead, the discovery of ultrahigh piezoelectricity in lead-free piezoelectric materials is critical for the substitution of commercial lead zirconate titanate (PZT) ceramics in numerous electronics. In this work, a synergistic design strategy is proposed to enhance the piezoelectricity in lead-free piezoelectric materials by flattening the Gibbs free energy density profile, via the coexistence of multiple phases and local structural heterogeneity Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(65 citation statements)
references
References 46 publications
0
65
0
Order By: Relevance
“…For instance, Ba 0.85 Ca 0.15 Zr 0.10 Ti 0.90 O 3 [ 33 ], BiFeO 3 [ 34 ] and (K, Na)NbO 3 -based [ 35 37 ] materials were reported to fabricate piezoelectric nanogenerators for energy harvesting and human motion sensing. Recently, it is found that stannum-doped BaTiO 3 (BTS) ferroelectric ceramics have the highest piezoelectric coefficient ( d 33 ) in lead-free piezoceramics with a low Curie temperature ( T c ) of ~ 40 °C[ 38 ]. It is well known that the sensors based on hard ceramics will lose piezoelectricity due to the depolarization phenomenon once the work temperature is higher than T c .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ba 0.85 Ca 0.15 Zr 0.10 Ti 0.90 O 3 [ 33 ], BiFeO 3 [ 34 ] and (K, Na)NbO 3 -based [ 35 37 ] materials were reported to fabricate piezoelectric nanogenerators for energy harvesting and human motion sensing. Recently, it is found that stannum-doped BaTiO 3 (BTS) ferroelectric ceramics have the highest piezoelectric coefficient ( d 33 ) in lead-free piezoceramics with a low Curie temperature ( T c ) of ~ 40 °C[ 38 ]. It is well known that the sensors based on hard ceramics will lose piezoelectricity due to the depolarization phenomenon once the work temperature is higher than T c .…”
Section: Introductionmentioning
confidence: 99%
“…These applications motivated researchers to investigate the existence of MPB in the novel promising ceramic compounds, e.g., PbHfO 3 –PbTiO 3 –Pb(Mg 1/3 Nb 2/3 )O 3 , [ 10,11 ] lead‐free BiFeO 3 –BaTiO 3 , [ 12,13 ] Pb(In 1/2 Nb 1/2 )O 3 –Pb(Mg 1/3 Nb 2/3 )O 3 –PbTiO 3 , [ 14 ] PbSnO 3 –Pb (Mg 1/3 Nb 2/3 )O 3 –PbTiO 3 , [ 15 ] and BiScO 3 –PbTiO 3 –Pb(Cd 1/3 Nb 2/3 )O 3 , [ 16 ] and even present new methods to induce MPB into the ordinary FE ceramics, e.g., BaTiO 3 . [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Parameters such as the length and distance between the dipoles in the piezoelectric sensor change with the applied force, resulting in an increase in the charge and voltage. [20][21][22][23] Therefore, piezoelectric sensors require no additional power supply. They have a high sensitivity and a fast response speed to dynamic pressure.…”
mentioning
confidence: 99%